Jamiat Haryono, Rusdi Lamsudin, Bambang Suryoatmojo - Assessing Glasgow Coma Scale (GCS) on patients with altered consciousness. - Jamiat Haryono, Jamiat Haryono (Universitas Gadjah Mada, 1999)
Background: Since its introduction in 1974, the Glasgow Coma Scale (GCS) has gained widespread acceptance around the world as a means of assessing the level of consciousness of patients with head injury. The reports have been widely accepted as evidence that the GCS is reliable when used by physicians and nurses.Objectives: To determine the interobserver agreement on GCS between doctor and nurse on assessing the altered consciousness.Methods: Thirty-seven patients with altered consciousness, who were admitted to the Department of Neurology, Dr. Sardjito General Hospital Yogyakarta, were observers by a physician and a nurse. Each patient was assessed separately by the observers. Complete forms were not shown or discussed, but were collected and put in a sealed enveloped. Statistical analysis: The statistics used to measure the levels of agreement was based on the formula developed by Fleiss.Result: The agreement of all items was almost perfect (K range from 0.74 to 0.90; p < 0.0001). Conclusions: The GCS was reliable as an objective tool for assessing altered consciousness.Key words : inter-rater agreement - Glasgow Coma Scale - consciousness